2015
DOI: 10.1007/s13204-015-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

A facile biomimetic preparation of highly stabilized silver nanoparticles derived from seed extract of Vigna radiata and evaluation of their antibacterial activity

Abstract: The significant antibacterial activity of silver nanoparticles draws the major attention toward the present nanobiotechnology. Also, the use of plant material for the synthesis of metal nanoparticles is considered as a green technology. In this context, a non-toxic, eco-friendly, and cost-effective method has been developed for the synthesis of silver nanoparticles using seed extract of mung beans (Vigna radiata). The synthesized nanoparticles have been characterized by UV-visible spectroscopy (UV-Vis), Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…As a naturally occurring resource, it is additionally less costly and abundantly available in the environment. Figure shows several plant extracts used to synthesize AgNPs from their leaves, seeds, roots, and fruits . In the following, several plant extracts used in various studies to produce AgNPs and are of interest are described.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a naturally occurring resource, it is additionally less costly and abundantly available in the environment. Figure shows several plant extracts used to synthesize AgNPs from their leaves, seeds, roots, and fruits . In the following, several plant extracts used in various studies to produce AgNPs and are of interest are described.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Synthesis of silver nanoparticles using plant extracts: (a) Abutilon indicum , (b) Skimmia laureola , (c) Lantana camara , (d) Prunus yedoensis , (e) Adenium obesum , (f) Coffea arabica , (g) Bunium persicum , (h) Vigna radiata , (i) Artocarpus heterophyllus Lam, (j) Jatropha curcas , (k) Ocimum sanctum , (l) Morinda citrifolia , (m) beetroot, (n) Justicia Adhatoda , (o) Zingiber officinale , (p) Vitis vinifera , (q) Crataegus douglasii , (r) Emblica Officinalis , (s) Terminalia chebula , and (t) Piper longum …”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…The characteristic peak of grape seed extract mediated synthesis, found at 440 nm, has also been reported by many researchers working with AgNPs. This absorption band was observed for AgNPs synthesised with Mukia maderaspatana, Kedrostis foetidissima and Cayratia pedata 28 , Euphorbia helioscopia Linn 29 , seed extract of Calendula officinalis 30 , seed extract of Vigna radiate 31 and Elettaria cardamomom seed extract 32 .…”
Section: Fig 2: Absorption Spectrum Of Silver Nanobioconjugates Ofmentioning
confidence: 85%
“…Figure 3 demonstrates typical TEM images of biosynthesized AuNPs, which depict that the AuNPs were poly dispersed and mostly spherical, while few of the particles were observed to be having irregular shapes. Such variations in morphologies and sizes of biogenic nanoparticles are quite common (Gangula et al 2011;Choudhary et al 2016). TEM analysis further revealed that majority of AuNPs had an average size around 18-20 nm.…”
Section: Tem Analysismentioning
confidence: 89%
“…For instance, the catalytic reduction and degradation of various dye pollutants using metal nanoparticles (MNPs) such as Cu, Ag, Au, Pd and Pt has been reported (Gangula et al 2011;Sahoo et al 2014;Kumari et al 2015;Yang et al 2015). Various biogenic synthesis routes have been employed in the fabrication of noble MNPs using Cylindrocladium floridanum and Penicillium fungus (Sadowski et al 2008;Narayanan et al 2013), Vigna radiata seed extract (Choudhary et al 2016), Catharanthus roseus leaf extract (Kalaiselvi et al 2015), Solanum lycopersicums fruit extract (Umadevi et al 2013), Cocos nucifera coir extract (Roopan et al 2013), Artemisia nilagirica leaf extract (Vijayakumar et al 2013), etc. In this report, we have reported the phytochemical preparation of (AuNPs) utilizing aqueous seeds extract of Foeniculum vulgare (fennel seeds). Fennel is a flowering herbaceous plant which belongs to the Apiaceae family.…”
Section: Introductionmentioning
confidence: 99%